Second-Generation Immigrants and Native Attitudes Toward Immigrants in Europe - Oscar Barrera; Isabelle Bensidoun; Anthony Edo (Institute of Labor Economics (IZA), 2022)
This paper investigates the role played by immigrants and their children in shaping native attitudes toward immigrants in the European Union. By exploiting the 2017 Special Eurobarometer on immigrant integration, we show that countries with a relatively high share of immigrants are more likely to believe that immigrants are a burden on the welfare system and worsen crime. In contrast, native opinions on the impact of immigration on culture and the labor market are unrelated to the presence of immigrants. We also find that the effects of second-generation immigrants on pro-immigrant attitudes toward security and fiscal concerns are positive (as opposed to first-generation immigrants). Finally, we find no impact of the immigrant share on the attitudes of natives supporting far-left or left political parties, while it is the most negative among respondents affiliated with far-right parties.
Keywords: F22; J15; P16; 330; immigration; second-generation immigrants; attitudes toward immigrants; public opinion